Tandem Repeat Analysis for Surveillance of Human Salmonella Typhimurium Infections - Torpdahl, Mia (Centers for Disease Control and Prevention, 2007)
In Denmark, as part of the national laboratory-based surveillance system of human enteric infections, all Salmonella Typhimurium isolates are currently subtyped by using phage typing, antimicrobial resistance profiles, and pulsed-field gel electrophoresis (PFGE). We evaluated the value of real-time typing that uses multiple-locus-number tandem-repeats analysis (MLVA) of Salmonella enterica serotype Typhimurium (S. Typhimurium) to detect possible outbreaks. Because only a few subtypes identified by PFGE and phage typing account for most infections, we included MLVA typing in the routine surveillance in a 2-year period beginning December 2003. The 1,019 typed isolates were separated into 148 PFGE types and 373 MLVA types. Several possible outbreaks were detected and confirmed. MLVA was particularly valuable for discriminating within the most common phage types. MLVA was superior to PFGE for both surveillance and outbreak investigations of S. Typhimurium.